Lived experiences and perspectives of women who had undergone perinatal loss in Nairobi county, Kenya: a qualitative study - Emily Wanja Kaburu; Christopher O Aimakhu; Thomas Matenjwa Kamau; Michael Omondi Owor (BMJ Public Health)
Background This study explored the lived experiences and perspectives of women who had suffered a perinatal loss in Nairobi county, Kenya. Existing research works have established that perinatal loss often comes with a significant psychosocial burden, which has been made worse by negative cultural beliefs and practices. Despite this, perinatal loss grieving is rarely recognised or socially legitimated in many countries. This study aimed to shed light on the experiences of bereaved women to come up with effective interventions and combat the stigma associated with perinatal loss.Methods The study used a qualitative research design employing a descriptive phenomenological approach targeting women of reproductive age who had experienced perinatal loss within the previous 3 years. The study was conducted in three subcounties of Nairobi. Purposive sampling was used to identify and recruit 22 women to participate in focus group discussions. After the discussions, the audio recordings were transcribed, translated and analysed thematically. Triangulation was then done per thematic area to allow for a deeper understanding of the experiences and perceptions of the study participants.Results The research identified 3 themes and 7 subthemes: (1) ‘Psychosocial challenges of perinatal loss’ with five subthemes;—‘Emotional trauma and grief’, ‘Multiple losses and reproductive pressure’, ‘Broken relationships,’ ‘Violence and abuse’ and ‘Familial stigmatization’. (2) ‘Healthcare experiences.’ (3) ‘Stigma and cultural influences’ with 2 subthemes ‘Societal stigmatisation’, and ‘Cultural perceptions and norms surrounding perinatal loss’.Conclusion Women who have experienced perinatal loss often suffer psychological torture, discrimination, abuse, stigma and trauma. The findings from this study highlight the urgent need to set-up robust support systems to assist individuals coping with perinatal loss. This will require a range of interventions, including implementing trauma management programmes, training of healthcare workers, advocacy, sensitisation and establishing support networks to address discrimination and stigma faced by those affected.